Hubungan Indeks Osilasi Selatan dan Indeks Curah Hujan terhadap Kejadian Kekeringan di Kabupaten Indramayu, Jawa Barat, Indonesia - BOEDI TJAHJONO; BABA BARUS; NINA WIDIANA DAROJATI (P4W LPPM IPB, 2017)
Indramayu district experiences frequent droughts that leads to many paddy fields harvest failure. Since the district is one of the national granary, this disaster needs to be addressed urgently. This study aimed to assess the level of dryness in Indramayu using Standard Precipitation Index (SPI) and its relation with the Southern Oscillation Index (SOI). The study used monthly rainfall data from 1996 to 2013 observed by 19 stations and the score of SOI that came from the Bureau of Meteorology of Australia. The method used quantitative approach using SPI and software SPI_sl_6.exe. Drought indices was measured in four different time scale which are 1, 3, and 6 month(s) (for the short term period) and the 12 months time scale (for the long term period). SPI’s assessment was classified in accordance with the classification of WMO (World Meteorological Organization) which consist of seven classes, ranging from wet extreme to dry extreme class. The results showed that the occurence of